In Situ Assembly of Octahedral Fe(II) Complexes for the Enantiomeric Excess Determination of Chiral Amines Using CD spectroscopy - Dragna, Justin (2012)
A method for discriminating between α-chiral primary amine enantiomers is reported. The method utilizes circular dichroism spectroscopy and a sensing ensemble composed of 2-formyl-3-hydroxyl pyridine (4) and Fe(II)(TfO)(2). Aldehyde 4 reacts rapidly with chiral amines to form chiral imines, which complex Fe(II) to form a series of diastereomeric octahedral complexes that are CD active in both the UV and visible spectrum. NMR studies showed that, for enantiomerically pure imine complexes, the Δ-fac isomer is preferred. A statistical analysis of the distribution of stereoisomers accurately models the calibration curves for enantiomeric excess. CD signals appearing in the UV region were bisignate, and the null of the CD signals were coincident with maxima in the UV spectrum, consistent with exciton coupling. TTDFT and semi-empirical calculations confirmed that the CD signals in the UV region arise from coupling of the π-π* transitions in the imine chromophores, and can be used to accurately describe the sign and magnitudes of the curves. The CD signals in the visible region arise from metal-to-ligand charge transfer bands, and these signals can be used to determine the ee values of chiral amines with an average absolute error of ±5%. Overall, the strategy presented herein represents a facile in situ assembly that uses commercially available simple reagents to create large optical signals indicative of ee values.